PEMERIKSAAN TINGKAT sdLDL SERUM SEBAGAI PETANDA DIAGNOSTIK STENOSIS KORONER (Serum sdLDL Level as A Diagnostic Marker of Coronary Stenosis) - Indranila K Samsuria; Laily Adninta (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Small dense LDL (sdLDL) is the LDL which particles are small and dense, it is pro-atherogenic. Increased levels of serum sdLDL areassociated with an increased risk of coronary stenosis. The aim of this study was to examine the diagnostic value of sd LDL in coronarystenosis. An analytical observational study with cross sectional approach was conducted at the Department of Clinical Pathology, MedicalFaculty of Diponegoro University/Dr. Kariadi Hospital and the Unit of Cardiac diseases during the period of March-October 2013. Thesubjects were 39 patients suspected of suffering a coronary stenosis. The diagnosis of coronary stenosis, degree of stenosis and numberof vascular stenosis was established at the time of cardiac catheterization. SdLDL assessment used a test kit. The statistical analysis usedwere unpaired t-test, Spearman correlation test, ROC analysis and diagnostic test. LDL levels in stenosis subjects, 35.4±9.01 mg/dL weresignificantly higher compared to levels in subjects that had no stenosis, 20.7±7.10 mg/dL (p<0.001; unpaired t-test). Correlation testresults showed a correlation between levels of serum sdLDL with severe degree of stenosis (correlation coefficient -0.64, p <0.001) and amoderate positive correlation between the number of vascular stenosis (Coefficient correlation 0.46; p=0.003; Spearman Correlation’sTest). The area under the curve of ROC was 0.9 (p <0.001). The cut off levels sdLDL were used to detect stenosis. The results showeda sensitivity of 85.2%, specificity of 75%, positive predictive value of 88.5%, negative predictive value of 69.2% and accuracy of 82%.Levels of serum sdLDL were associated with severe to extensive stenosis degree, and showed a good diagnostic value, thus, it can beused for screening to determine the presence of coronary stenosis.